Pengaruh Green Accounting, Kinerja Lingkungan dan Ukuran Perusahaan Terhadap Financial performance (Studi Kasus pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2018) - Eka Mutia Anin Dita; Deasy Ervina (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2021)
The mining sectorial is an industry that directly related to nature so the activities carried out will have an impact on enviromental sustaibibility around it. If the company take so much care to enviromental factor maybe there is an impact to firm’s financial performance. This study aims to examine and anlyze the effect of green accounting, enviromental performance and firm size on the financial performance of companies that listed on Indonesian Stock Exchange from 2017-2018 in mining sector. This research using a purposive sampling methode which has 34 firm samples. The result show that green accounting has no effect to financial performance, enviromental performance effects on financial performance and firm size has no effect to financial performance. Keywords :Green Accounting; Enviromental Performance; Firm Size; Financial performance